Hubungan Personal Hygiene Dengan Kejadian Penyakit Kusta Di Rumah Sakit Khusus Kusta Dr Sitanala Kota Tangerang Tahun 2015 - Sri Komalaningsih (stikes dharma husada bandung, 2016)
Leprosy is an infectious disease still prevalent in developing countries, including at Indonesia. In this study the problem is personal hygiene factor in leprosy patients in dr. Sitanala Leprosy Special Hospital Tangerang City. The purpose of this research was to determine the relationship between personal hygiene with occurrence of leprosy in dr. Sitanala Leprosy Special Hospital. This study uses a case-control approach. The population was outpatients in dr. Sitanala Leprosy Special Hospital diagnosed leprosy (cases) and Diabetes Mellitus (control). Samples are 108 patients. The instrument used was questionnaire. Data were analyzed with Chi-square test formula. The research results that there was a relationship between hand washing habits (p=0,023, OR=3,357) but there were not relationship bathing habits (p=0,066, OR=2,340), towel cleaning habits (p=0,740,OR=1,563), cloth cleaning habits (p=0,525, OR=1,862) and bed, blanket , pillow cases cleaning (p=0,171, OR=2,105) with occurrence of leprosy in dr. Sitanala Leprosy Special Hospital. Suggestion put forward is expected to improve personal higiene the patient and who live around them expecially on seven step hand washing habit according WHO so as not to be a source of transmission of leprosy.